Evaluation of in Vitro Corrosion Behavior of Titanium Oxynitride Coated Stainless Steel Stents - Saqib, Muhammad; Kuzmin, Oleg S.; Kraskiewicz, Honorata; Wasyluk, Lukasz; Cuniberti, Gianaurelio (Giovanni); Ficai, Anton A.; Pichugin, Vladimir F.; Opitz, Joerg; Beshchasna, Natalia (IEEE Access, 2021)
Coronary artery disease (CAD) affects every fifth person in the world. The gold-standard treatment for CAD is stent implantation, however, the existing therapy is not sufficient. In recent years, titanium oxynitride (TiOxNy) coatings on bare metal stents (BMSs) attracted the attention of many researchers around the world due to their promising results and improved surface properties. However, good coating adhesion and coverage of the inner surface in stent applications is still a challenging task. Moreover, enhanced corrosion resistance and durability over a longer period under the influence of an aggressive biological environment is one of the main requirements while developing novel coatings for bare-metal stents. In this work, the titanium oxynitride (TiOxNy) coated stainless steel stents were fabricated by magnetron sputtering and the corrosion behavior of coated and uncoated stents has been studied using immersion, fluid dynamic, and electrochemical corrosion tests. For the first time, the entire stent surface has been used for quantitative corrosion tests on stents. We discuss and compare the in vitro biostability and corrosion behavior of bare stainless steel (316L) and titanium oxynitride films (TiOxNy) coated stents.TiOxNy coatings provide valuable stability to the BMS against harsh environments or conditions. The coated stents are remarkably more stable when compared with the reference uncoated stents (316L BMS), regardless of the ratio of O2 and N2. The variation of stent coating parameters is still possible to get more anticorrosive and biostable behavior; therefore, the results could provide the basis for further research.
CRIS-Team Scopus Importer:2022-04-14
Keywords: bare-metal stent; Coronary artery disease; corrosion resistance; titanium oxynitride coating